The Ecology of Power: Culture, Place and Personhood in the Southern Amazon, AD 1000–2000 - Heckenberger, Michael J. (Critical perspectives in identity, memory, and the built environment, 2005)
In 1884 a community of Brazilians was "discovered" by the Western world. The Ecology of Power examines these indigenous people from the Upper Xingu region, a group who even today are one of the strongest examples of long-term cultural continuity. Drawing upon written and oral history, ethnography, and archaeology, Heckenberger addresses the difficult issues facing anthropologists today as they "uncover" the muted voices of indigenous peoples and provides a fascinating portrait of a unique community of people who have in a way become living cultural artifacts. Michael Heckenberger is Assistant Professor in the Department of Anthropology at the University of Florida--Gainesville. He has recieved numerous research grants and is principal investigator in the Southern Amazon Ethno-archaeological Project. He is co-author of the forthcoming Archaeology of the Amazon (Cambridge University Press).